The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3176/earth.2015.27
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir quality and petrophysical properties of Cambrian sandstones and their changes during the experimental modelling of CO2storage in the Baltic Basin

Abstract: The objectives of this study were (1) to review current recommendations on storage reservoirs and classify their quality using experimental data of sandstones of the Deimena Formation of Cambrian Series 3, (2) to determine how the possible CO 2 geological storage (CGS) in the Deimena Formation sandstones affects their properties and reservoir quality and (3) to apply the proposed classification to the storage reservoirs and their changes during CGS in the Baltic Basin.The new classification of the reservoir qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…A low-quality reservoir has a permeability of less than 10 mD and a porosity of less than 10%. A recent classification proposed by Shogenov et al 47 suggested a different approach to classification. They defined two levels for a high-quality reservoir that can be used for carbon storage.…”
Section: Reservoir Containmentmentioning
confidence: 99%
“…A low-quality reservoir has a permeability of less than 10 mD and a porosity of less than 10%. A recent classification proposed by Shogenov et al 47 suggested a different approach to classification. They defined two levels for a high-quality reservoir that can be used for carbon storage.…”
Section: Reservoir Containmentmentioning
confidence: 99%
“…According to the permeability and porosity data of the studied rocks (Fig. 15) plotted in the classification scheme proposed by Shogenov et al (2015), It is observed that the rocks of the Cogollo Group are classified as reservoirs of low porosity (Class VII, 1-10 mD of permeability and 7-18 % of porosity) to very low porosity (Class VIII, < 1 mD of permeability and < 18 % of porosity). According to the classification of Zou et al (2012), it is observed that the Cogollo Group siliciclastic rocks meet all the criteria to be classified as tight sand reservoirs (medium diagenetic evolution, secondary porosity, porosity between 3-12% and permeabilities less than 0.1 mD).…”
Section: Quality As Reservoir Rockmentioning
confidence: 99%
“…15. Porosity vs permeability diagram with the reservoir quality classification according to Shogenov et al (2015) for the rocks of the present study.…”
Section: N P R E S Smentioning
confidence: 99%
“…These properties are catalogued by Shogenov et al (2015) as average to good quality hydrocarbon reservoirs (Ø (%)19-25.5; K(mD) 113-295.5). Our study documents some intervals, presenting the most common porosity and permeability values in productive reservoirs (Ø (%) 15-25), according to Dikkers (1985).…”
Section: La Loma Syncline Areamentioning
confidence: 99%